2020
DOI: 10.1039/d0ra01093f
|View full text |Cite
|
Sign up to set email alerts
|

Highly-selective solvent-free catalytic isomerization of α-pinene to camphene over reusable titanate nanotubes

Abstract: Titanate nanotubes prepared by hydrothermal reconstitution and post-modification with HCl aqueous solution were studied in α-pinene isomerization showing high selectivity to camphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…On the contray, protonated titanate nanotubes was reported as solid acid catalyst for conversion of glucose into HMF via isomerization and dehydration process, giving the moderate yield of HMF ( Kitano et al, 2010 ). Recently, protonated titanate nanotubes exhibit relatively high catalytic performance for isomerizaiton of alpha pinene, an inexpensive and important essential oil which is widely used in the synthesis of various fine chemicals ( Huang et al, 2020 ). Hence, it is believed that the protonated titanate nanotubes/sodium titanate nanotubes can be uesed as acid or base catalyst in different types of isomerization reactions for bio-based chemicals production.…”
Section: Biomass Derived Chemicals Productionmentioning
confidence: 99%
“…On the contray, protonated titanate nanotubes was reported as solid acid catalyst for conversion of glucose into HMF via isomerization and dehydration process, giving the moderate yield of HMF ( Kitano et al, 2010 ). Recently, protonated titanate nanotubes exhibit relatively high catalytic performance for isomerizaiton of alpha pinene, an inexpensive and important essential oil which is widely used in the synthesis of various fine chemicals ( Huang et al, 2020 ). Hence, it is believed that the protonated titanate nanotubes/sodium titanate nanotubes can be uesed as acid or base catalyst in different types of isomerization reactions for bio-based chemicals production.…”
Section: Biomass Derived Chemicals Productionmentioning
confidence: 99%
“…30,31 Research by Geng Huang et al showed that the catalyst's grain size significantly affects the catalytic activity. 32 For this experimental system, the grain size and the type of the titanium-based precursor will play a vital role in the pore structure and acidity of the acid-activated catalyst. However, no details about the effect of catalyst grain size on activity have been reported.…”
Section: Introductionmentioning
confidence: 99%